Continuous Reassortment of Clade 2.3.4.4 H5N6 Highly Pathogenetic Avian Influenza Viruses Demonstrating High Risk to Public Health - Huanan Li; Qian Li; Bo Li; Yang Guo; Jinchao Xing; Qiang Xu; Lele Liu; Jiahao Zhang; Wenbao Qi; Weixin Jia; Ming Liao (Pathogens, 2020)
Since it firstly emerged in China in 2013, clade 2.3.4.4 H5N6 highly pathogenic avian influenza viruses (HPAIVs) has rapidly replaced predominant H5N1 to become the dominant H5 subtype in China, especially in ducks. Not only endemic in China, it also crossed the geographical barrier and emerged in South Korea, Japan, and Europe. Here, we analyzed the genetic properties of the clade 2.3.4.4 H5N6 HPAIVs with full genome sequences available online together with our own isolates. Phylogenetic analysis showed that clade 2.3.4.4 H5N6 HPAIVs continuously reassorted with local H5, H6, and H7N9/H9N2. Species analysis reveals that aquatic poultry and migratory birds became the dominant hosts of H5N6. Adaption to aquatic poultry might help clade 2.3.4.4 H5N6 better adapt to migratory birds, thus enabling it to become endemic in China. Besides, migratory birds might help clade 2.3.4.4 H5N6 transmit all over the world. Clade 2.3.4.4 H5N6 HPAIVs also showed a preference for α2,6-SA receptors when compared to other avian origin influenza viruses. Experiments in vitro and in vivo revealed that clade 2.3.4.4 H5N6 HPAIVs exhibited high replication efficiency in both avian and mammal cells, and it also showed high pathogenicity in both mice and chickens, demonstrating high risk to public health. Considering all the factors together, adaption to aquatic poultry and migratory birds helps clade 2.3.4.4 H5N6 overcome the geographical isolation, and it has potential to be the next influenza pandemic in the world, making it worthy of our attention.